Peran Kepala Sekolah dalam Meningkatkan Kompetensi Guru di SDN 1 Teko - Howin Hendria Santana (Jurnal Prasasti Ilmu, 2026)
This study aims to analyze the role of the principal in improving teacher competency at SDN 1 Teko. Improving teacher competency is a crucial factor in improving the quality of education, thus requiring effective principal leadership to support continuous teacher professional development. This study employed a qualitative descriptive approach, with the research location at SDN 1 Teko. Research informants consisted of principals and teachers purposively selected based on their involvement in teacher competency development programs. Data were collected through observation, in-depth interviews, and documentation. Data validity was tested using source triangulation and technical triangulation, while data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results showed that the principal plays a significant role in improving teacher competency through seven main leadership functions. As an educator, the principal provides role models, fosters discipline, and provides learning assistance. As a manager, the principal plans, organizes, implements, and supervises teacher development programs. As an administrator, the principal manages learning administration and provides feedback on teacher teaching materials. As a supervisor, the principal conducts classroom observations and academic coaching. As a leader, the principal implements open, participatory, and transparent leadership. As an innovator, the principal encourages teachers to participate in training, participate in Teacher Working Group (KKG) activities, and develop innovative learning. As a motivator, the principal provides rewards and moral support to boost teacher morale. Research findings indicate that the integration of these various leadership roles positively contributes to improving teachers' pedagogical, professional, social, and personal competencies and supports improvements in the quality of education at SDN 1 Teko.